DEMOKRASI VIRTUAL DAN PERANG SIBER DI MEDIA SOSIAL: PERSPEKTIF NETIZEN INDONESIA - Iswandi Syahputra (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2017)
Several hate speech which spread in social media activity aroused because of freedom of speech euphoria in a democratic nation. Those hate speech had effectively used as a negative campaign during election. This study aims to analyze hate speech and cyber war in social media. The method used is qualitative with data retrieval through in-depth interviews of netizens as opinion makers in social media, document studies and literature studies relevant to the research. The study found that cyber warfare in social media has formed two netizen polarizations. The polarization can be identified as conservative and liberal groups. Both groups are actively producing discourse, opinion, information, issues and rumors through social media. This study has implications for the change or shift of opinion leader concept on the theory of two step communication. The concept of opinion maker in the new media tradition that emerges today allows anyone anonymously to become opinion leaders.